1991
DOI: 10.1111/j.1748-5827.1991.tb00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up study of 100 cases with thoracolumbar disc protrusions treated by lateral fenestration

Abstract: One hundred‐and‐seventeen dogs with thoracolumbar disc protrusions were treated by lateral fenestration over a five year period. The results obtained in 100 of these cases are presented. The overall success rate was 87 per cent but only 33 per cent of those with paraplegia and loss of conscious pain sensation regained the use of their hindlimbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 8 publications
7
61
0
Order By: Relevance
“…The main disadvantages of fenestration are that recovery rates and times are prolonged for dogs with grade 3 and 4 deficits compared to decompression (Butterworth and Denny, 1991;Davies and Brown, 2001) (Tables 8.1, 8.2). Results are much worse than decompression for dogs with grade 5 deficits (Table 8.1).…”
Section: Fenestration Without Decompressionmentioning
confidence: 99%
“…The main disadvantages of fenestration are that recovery rates and times are prolonged for dogs with grade 3 and 4 deficits compared to decompression (Butterworth and Denny, 1991;Davies and Brown, 2001) (Tables 8.1, 8.2). Results are much worse than decompression for dogs with grade 5 deficits (Table 8.1).…”
Section: Fenestration Without Decompressionmentioning
confidence: 99%
“…The use of multiplc prophylactic disc fenestration in conjunirion with decompressive surgery is contiovcrsial and its eficacy has been disputed by some workers (Brown and others 1977, Prara 1981, Fingeroth 1989. Disc fenestration has been shown to reduce significantly the likelihood of recurrence in some studies (Davies andSharp 1983, Butterworth andDenny 1991) but n o t in another (Levineand Caywood 1984).…”
Section: Radiographymentioning
confidence: 99%
“…The approach to an individual case will be influenced by the proper staging of the disease (Davies and Sharp 1983, Wheeler 1989, Butterworth and Denny 1991. The duration of clinical signs and economic factors will also influence the decision of whether to intervene surgically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have shown that the postoperative recovery rate of surgical decompression conducted on dogs with severe IVDH associated with loss of pain perception and paraplegia, to vary between 33% and 76%. 4,[10][11][12][13] The recovery rate of the BM-MNC transplant group in this study also was markedly higher when compared to the rates reported by other researchers. The canine spinal column consists of 7 cervical vertebrae (7 in humans), 13 thoracic vertebrae (12 in humans), 7 lumbar vertebrae (5 in humans), and sacral vertebrae.…”
Section: Discussionmentioning
confidence: 68%